Imatinib, a New Adjuvant Medical Treatment for Multifocal Villonodular Synovitis Associated to Noonan Syndrome: A Case Report and Literature Review - Dalla-Torre, Romain; Crenn, Vincent; Menu, Pierre; Isidor, Bertrand; Guillot, Pascale; Le Goff, Benoit; Geffroy, Loic; Dauty, Marc; Fouasson-Chailloux, Alban (Frontiers in Medicine, 2022)
Noonan syndrome (NS) is an autosomal dominant multisystem disorder caused by the dysregulation of the Rat Sarcoma / Mitogen-activated protein kinase (RAS/MAPK) pathway and characterized by short stature, heart defects, pectus excavatum, webbed neck, learning disabilities, cryptorchidism, and facial dysmorphia. Villonodular synovitis is a joint disorder most common in young adults characterized by an abnormal proliferation of the synovial membrane. Multifocal Villonodular synovitis is a rare disease whose recurrent nature can make its management particularly difficult. Currently, there is no systemic therapy recommended in diffuse and recurrent forms, especially because of the fear of long-term side effects in patients, who are usually young. Yet, tyrosine kinase inhibitors seem promising to reduce the effects of an aberrant colony stimulating factor-1 (CSF-1) production at the origin of the synovial nodule proliferation. We present here the case of a 21-year-old woman with NS associated to diffuse multifocal villonodular synovitis (DMVS). Our clinical case provides therapeutic experience in this very rare association. Indeed, in association with surgery, the patient improved considerably: she had complete daily life autonomy, knee joint amplitudes of 100° in flexion and 0° in extension and was able to walk for 10 minutes without any technical assistance. To our knowledge, this is the first case of a patient suffering from DMVS associated with a Noonan syndrome treated with Glivec® (oral administration at a dosage of 340 mg/m2 in children, until disease regression) on a long-term basis.